Kansanperinne 2.0 Sukelluksia 2000-luvun vernakulaariin kulttuuriin - Koski, Kaarina; Hovi, Tuomas (Tietolipas, 2023)
In the 21st century, vernacular tradition has been emerging updated, hybridized forms. The increased availability of digital devices and resources has diminished the gap between professional production and folk culture. Digital technology and commercial productions have merged with grassroots practices, local identities, and personal expression. This book introduces analytical views of contemporary folklore as vernacular meaning-making and performance in interaction with digital technology and commercial productions. It focuses on various genres, such as internet memes, local rap music, video games, creepypasta, and stand-up performances. Central themes featured in the analyses include accelerated cultural circulation and reinterpretations, questions surrounding ownership and appropriation, technological agency, and the performance of cultural and personal identities.